Tying under Double-Marginalization - Roman Inderst; Fabian Griem; Greg Schaffer (ZBW - Leibniz Information Centre for Economics, 2022)
In a model of contractual inefficiencies due to double-marginalization, we analyze the practice of tied rebates that incentivizes retailers to purchase multiple products from the same manufacturer. We isolate two opposing effects: a surplus-sharing effect that enhances efficiency and a rent-extraction effect that reduces efficiency. The overall effect is more likely to be negative when the manufacturer has a particularly strong brand for which the retailers alternatives are much inferior. Foreclosure of a more efficient provider of the manufacturers weaker product is not a sufficient condition for a welfare loss. Our key positive implication relates to the seemingly inefficient introduction of weaker products by the owners of particularly strong brands.
Keywords: L14; D43; 330; contractual inefficiencies; double-marginalization; competition; surplus-sharing effect; rent-extraction effect; efficiency; brand strength